Analisis Produksi dan Efisiensi Pengelolaan Tanaman Terpadu Padi Sawah di Provinsi Bali - Suharyanto, Suharyanto; Mulyo, Jangkung H.; Darwanto, Dwidjono H.; Widodo, Sri (Jurnal Penelitian Pertanian Tanaman Pangan, 2015)
The integrated crop management approach on rice is aimed to increase the productivity on fields with the constraint of limited land area. This present research was aimed to analyzethe impact of the implementation of integrated crop management to grain yield and its efficiency on the lowland farming. The study was conducted in three districts representing the lowland rice production center in Bali, i.e. Tabanan, Buleleng and Gianyar, involving 216 respondents, over two cropping seasons. Sampling of the respondents was using stratified simple random method. Data were analyzed using a stochastic frontier production function with the Maximum Likelihood Estimation (MLE) method. The results showed that the aggregate of rice production was affected by land area, amount of seeds, N fertilizer, organic fertilizer, pesticides, labor and age of seedling. Rice yield was higher in the dry season applying legowo planting pattern, followed by intermittent irrigations, IPM and planting varieties other than IR64. Technically, both ICMFS alumni farmers and non ICM-FS alumni were considered efficient, with an efficiency rate of more than 70 percent, but onlyICM-FS alumni farmers allocated the inputs efficiently, and therefore economically move efficient. Socio economic factors which were significantly affected the aggregate technicalinefficiencies were age of farmers, level of education, farming experiences, and the number of land plots. Technical inefficiency of the lowland rice farming was lower when ICM-FS alumni farmers work on their own lands.